‘Bushman’ bandits of the eastern borderlands: The rock art of raiders in the Eastern Cape, South Africa, in the eighteenth and nineteenth centuries - Sinclair-Thomson, Brent (My University, 2020)
This thesis focuses on rock art that was created in the Eastern Cape during the colonial period. It is possible to date the images by what is depicted –muskets, hats and horses. Using San, Khoe and other ethnographic sources, we can ‘see’, through indigenous eyes, how life was experienced on the colonial frontier (and in borderlands) as it moved into the Eastern Cape hinterland. Though hard to believe, this region, having been one of the first and most densely settled by colonists, has received almost no archaeological attention of this sort. The rock art images in question were seemingly made by those who actively resisted the colonial project – bandits or ‘guerrillas’ from mixed cultural backgrounds, each group having its own particular mosaic of individuals and therefore idiosyncratic modes of representation
A thesis submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Doctor of Philosophy, 2020